1989
DOI: 10.1159/000167938
|View full text |Cite
|
Sign up to set email alerts
|

Renal Concentration Defect Induced by Cisplatin

Abstract: The effects of cisplatin (5 mg/kg BW given intraperitoneal^) on renal concentration mechanism were evaluated initially by clearance studies in rats 5–7 days after cisplatin administration and compared to normal rats. During hypotonic saline infusion, cisplatin rats showed a lower inulin clearance (0.56 ± 0.07 vs. 1.12 ± 0.09 ml/min/100gBW, p < 0.01), a higher fractional distal delivery (CNa + CH20/Cin) (36.3 ± 4.4 vs. 22.8 ± 4.5%, p < 0.05), and lower CH20/CNa + CH20 (33.6 ± 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…These findings are not different from previously published data in which the marked polyuria has been identified in the cisplatin-induced ARF. [1][2][3][4] Clearance study indicated that GFR was decreased following cisplatin-treatment in rats. Moreover, the urinary creatinine excretion was attenuated in rats with cisplatin-in- A. B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are not different from previously published data in which the marked polyuria has been identified in the cisplatin-induced ARF. [1][2][3][4] Clearance study indicated that GFR was decreased following cisplatin-treatment in rats. Moreover, the urinary creatinine excretion was attenuated in rats with cisplatin-in- A. B.…”
Section: Discussionmentioning
confidence: 99%
“…ARF, when caused by cisplatin, is typically characterized by a nonoliguria, a severe reduction in glomerular filtration rate (GFR), a variable fall in renal blood flow, and a decrease in the urinary concentrating ability. [1][2][3][4] Certain pathophysiologic conditions associated with an altered urinary concentration have been related causally to an altered regulation of aquaporin (AQP) water channel in the kidney. [5][6][7][8] Several recent studies have provided convincing of reducing expression of renal aquaporin 2 (AQP 2) in rats with cisplatin-induced ARF.…”
mentioning
confidence: 99%
“…It has been reported that cisplatin elicited oxidative stress in and around mitochondria, thereby inducing apoptosis of renal proximal tubule cells and dysfunction of the kidney [4, 5, 6]. Cisplatin is a well-known renal tubular toxin, leading to increased excretion of a number of substances, including amino acids, glucose, phosphate, sodium, magnesium and L -carnitine [7, 8]. The mechanisms of this toxic effect may involve direct inhibition of specific membrane transport systems, mitochondrial toxicity and depletion of glutathione, finally leading to loss of specific functions and/or necrosis of renal tubular cells [9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is known to induce AKI in rats, which then exhibit oliguria, severe reduction in glomerular filtration rate (GFR), reduced renal blood flow, and damage to the renal urinary concentrating ability [17,18]. Several recent studies have indicated that L-carnitine is capable of preventing renal proximal tubular cell apoptosis, inhibiting mitochondrial respiration dysfunction and DNA injury, improving renal function, and elevating the GFR in rats with cisplatin-induced renal dysfunction [19].…”
Section: Discussionmentioning
confidence: 99%